2019
DOI: 10.3389/fmicb.2019.02737
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Rhinoviruses in Lower Respiratory Tract Infections in Children – Clinical and Molecular Epidemiological Study From Croatia, 2017–2019

Abstract: Rhinoviruses (RVs) are increasingly implicated not only in mild upper respiratory tract infections, but also in more severe lower respiratory tract infections; however, little is known about species diversity and viral epidemiology of RVs among the infected children. Therefore, we investigated the rhinovirus (RV) infection prevalence over a 2-year period, compared it with prevalence patterns of other common respiratory viruses, and explored clinical and molecular epidemiology of RV infections among 590 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…A recent prospective study conducted in 11 European countries has shown that in adults presenting to primary care with LRTI, the most common viral pathogens detected were human rhinoviruses (20.1%) (45). Another recent study conducted on hospitalized children with ARI in Croatia also revealed rhinovirus as the most frequently detected virus, diagnosed in 33.4% patients; 60.4% as monoinfection, and 39.6 % as co-infection with other respiratory viruses (46). More than half of children infected with rhinovirus (55.8%) presented with LRTI (46).…”
Section: Rhinovirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent prospective study conducted in 11 European countries has shown that in adults presenting to primary care with LRTI, the most common viral pathogens detected were human rhinoviruses (20.1%) (45). Another recent study conducted on hospitalized children with ARI in Croatia also revealed rhinovirus as the most frequently detected virus, diagnosed in 33.4% patients; 60.4% as monoinfection, and 39.6 % as co-infection with other respiratory viruses (46). More than half of children infected with rhinovirus (55.8%) presented with LRTI (46).…”
Section: Rhinovirusesmentioning
confidence: 99%
“…The complexity of these observations is emphasized by the finding that the relationship between species and disease severity also depends in some extent on age, i.e., it is frequently noted that RV-C tends to cause more severe disease in children (56) and HRV-A in adults (54). Most studies are however in agreement that RV-B tends to occur sporadically and often in asymptomatic patients (46,54,57).…”
Section: Rhinovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that retroviruses leading to neural involvement like HIV and HTLV-1 can cause tight junction disintegration ( Miller et al, 2012 ). Similarly, the Zika virus has been shown to alter BBB structure especially the tight junctions ( Ljubin-Sternak et al, 2019 ). Additionally, the virus has an important interaction with ACE-2 receptors located on both endothelium as well as brain vascular pericytes.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum likelihood phylogenetic trees were generated based on 594 cgMLST core genes and 8 MLST housekeeping genes in all 80 samples via TreeBeST under Hasegawa-Kishino-Yano (HKY) and general time-reversible (GTR) models (49)(50)(51). The reliability of the branching orders was evaluated via 1,000 bootstrap replicates (52). The Phylogenetic trees were annotated using Interactive Tree Of Life (iTOL) v5 (https://itol.embl.de/) (53).…”
Section: Methodsmentioning
confidence: 99%